The Relationship Between Knowledge With The Implementation Of Reproductive Organs Care - Elis Roslianti; Yanti Srinayanti; Susi Susilawati; Ade Fitriani (LPPM STIKes Muhammadiyah Ciamis, 2019)
According to WHO, reproductive health is a state of complete physical, mental and social well-being, not only free from disease or disability in all aspects related to the reproductive system, its functions and processes. Reproductive health is related to the cleanliness of the organs. Reproductive organs are very important to maintain cleanliness, it is also necessary to pay attention to how to maintain and care for them properly and correctly, especially in women. Women have reproductive systems that are sensitive to disease. Objective of This study aims to analyze the relationship between knowledge and the implementation of reproductive organ care in STIKes Muhammadiyah Ciamis S1 Nursing Study Program students. This type of research is an analytical survey with a Cross Sectional approach. The population in this study were second and third level students of the S1 Nursing Study Program at STIKes Muhammadiyah Ciamis. Samples were taken as many as 55 respondents using purposive sampling technique. The data collected consisted of primary data obtained through questionnaire sheets and direct observation and statistical analysis using Chi - Square.The results of the study: There is a relationship between knowledge and the implementation of reproductive organ care. With the Chi Square test, it can be concluded that the P Value of 0.007 <0.05, it can be concluded that Ho is rejected, which means that there is a significant relationship between knowledge and the implementation of reproductive organ care for undergraduate students of STIKes Muhammadiyah Ciamis.